2019
DOI: 10.18484/2305-0047.2019.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Anatomical Variations of Maxillary Sinus and Ostiomeatal Components Complex in Surgical Treatment of Sinusitis

Abstract: Харьковский национальный медицинский университет, г. Харьков, Украина Цель. Определение анатомической изменчивости верхнечелюстной пазухи и компонентов остиомеатального комплекса, а также подбор на основании полученных данных оптимального доступа к зоне гайморовой пазухи для выбора метода лечения гайморита, позволяющего минимизировать интра-и постоперационные осложнения.Материал и методы. Изучены результаты исследований околоносовых пазух 30 пациентов, проведенных на спиральном компьютерном томографе. Среди ни… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This combination can be especially dangerous in women during menopause [9]. The main prerequisite for the development of inflammatory processes in the paranasal sinuses is its inadequate ventilation [10]. Thus, it is extremely important to know the features of the anatomical variability of the components that make up the ostiomeatal complex.…”
Section: Discussionmentioning
confidence: 99%
“…This combination can be especially dangerous in women during menopause [9]. The main prerequisite for the development of inflammatory processes in the paranasal sinuses is its inadequate ventilation [10]. Thus, it is extremely important to know the features of the anatomical variability of the components that make up the ostiomeatal complex.…”
Section: Discussionmentioning
confidence: 99%
“…This inevitably entails a change in its microarchitectonics, thereby, a decrease in bone density, precipitating the the development of intracranial and intraorbital complications of rhinosinusitis. Moreover, a decrease in bone tissue density of the lower wall can lead to complications (Alekseeva et al 2019) during dental implantation due to improper load dosing during this procedure. The study showed that each patient required an individual approach to the diagnosis and treatment of rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical structure of the paranasal sinuses (PNSs) of a person predetermines the risk of development, diversity of presentation, possibility of complications and features of surgical treatment of their inflammation, rhinosinusitis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%